Depressive state as an initial symptom for subdural abscess. Issue 1 (17th December 2015) - Fukui, Takao; Ueda, Akihiro; Murate, Ken‐ichiro; Hikichi, Chika; Ito, Shinji; Asakura, Kunihiko; Mutoh, Tatsuro
Abstract: A 47‐year‐old man with a subdural abscess was initially diagnosed with endogenous depression at another hospital. He presented with a chronic illness, but without any typical symptoms, such as headache and fever. Antidepressants were ineffective and brain magnetic resonance imaging showed areas of abnormal high‐signal intensity along the surface of the bilateral frontoparietal lobes. We diagnosed him with a subdural abscess based on magnetic resonance imaging and cerebrospinal fluid findings, which was successfully managed with antibiotic treatment alone. This case highlights the possibility that depressive state can be an initial symptom of a subdural abscess.